Mars and the ESA Science Programme - the case for Mars polar science - Thomas, Nicolas; Becerra, P.; Smith, I. B. (Experimental Astronomy, 2022)
Current plans within the European Space Agency (ESA) for the future investigation of Mars (after the ExoMars programme) are centred around participation in the Mars Sample Return (MSR) programme led by NASA. This programme is housed within the Human and Robotic Exploration (HRE) Directorate of ESA. This White Paper, in response to the Voyage 2050 call, focuses on the important scientific objectives for the investigation of Mars outside the present HRE planning. The achievement of these objectives by Science Directorate missions is entirely consistent with ESA’s Science Programme. We illustrate this with a theme centred around the study of the Martian polar caps and the investigation of recent (Amazonian) climate change produced by known oscillations in Mars’ orbital parameters. Deciphering the record of climate contained within the polar caps would allow us to learn about the climatic evolution of another planet over the past few to hundreds of millions of years, and also addresses the more general goal of investigating volatile-related dynamic processes in the Solar System.